Towards the Economics of Sustainable Development - Ganowicz-Bączyk, Anita (Studia Ecologiae et Bioethicae, 2012)
Perceiving nature by contemporary social and economical systems, including the domination nowadays of capitalism and socialism, has led to an ecological crisis. There are at least several characteristics of traditional economical theories that make it impossible to realize the sustainable development of the anthroposphere, i.e. the view of a human being, the violation of rules of inter- and intragenerational justice, the way of valuing the environment combined with the underestimation of the significance of natural resources, the belief that technology is able to substitute all natural resources crucial to humanity, planning the short-term goals. Qe attitudes in economics appeared which demand replacing the current paradigm with a new one – that of strong sustainability. The characteristic feature of the economics of sustainable development is observing the ethical rules of inter- and intergenerational justice and responsibility.